2019
DOI: 10.1126/sciadv.aav6187
|View full text |Cite
|
Sign up to set email alerts
|

Autofocals: Evaluating gaze-contingent eyeglasses for presbyopes

Abstract: As humans age, they gradually lose the ability to accommodate, or refocus, to near distances because of the stiffening of the crystalline lens. This condition, known as presbyopia, affects nearly 20% of people worldwide. We design and build a new presbyopia correction, autofocals, to externally mimic the natural accommodation response, combining eye tracker and depth sensor data to automatically drive focus-tunable lenses. We evaluated 19 users on visual acuity, contrast sensitivity, and a refocusing task. Aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…An advantage of our device over other previously proposed 10 is the bigger power range of the tunable lenses used. A larger range allows to focus very close targets, going beyond the normal focus range of an adult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An advantage of our device over other previously proposed 10 is the bigger power range of the tunable lenses used. A larger range allows to focus very close targets, going beyond the normal focus range of an adult.…”
Section: Discussionmentioning
confidence: 99%
“…Padmanaban et al . have developed another solution using commercial parts for pupil tracking and depth sensing for the tunable lenses 10 . However, as far as we know their system is not truly a mobile solution since their pupil tracking processing (Pupil Labs GmbH, Berlin, Germany) is done on a high-end desktop PC.…”
Section: Introductionmentioning
confidence: 99%
“…For example, ETLs have been getting thinner and lighter. Recently, it was announced that a new ETL provides an aperture that is almost two times larger (30 mm) than the current one [41]. Therefore, we believe that the form factor of our system can be similar to typical eyeglasses in near future, which solves the FOV problem.…”
Section: Discussionmentioning
confidence: 83%
“…Smart-eyeglasses consist of three main electronic components – sensors, embedded computing systems and adjustable focus lenses. They use a host of sensors to determine the object distance 9,10,12 and the gaze (point of visual focus) of every eye 11,13 . Using this data, the embedded computing systems within these devices can near-instantaneously change the optical power of the adjustable-focus lenses by performing quick calculations which use real-time sensor data and electronically-stored accommodation data of the patient.…”
Section: Introductionmentioning
confidence: 99%
“…Using this data, the embedded computing systems within these devices can near-instantaneously change the optical power of the adjustable-focus lenses by performing quick calculations which use real-time sensor data and electronically-stored accommodation data of the patient. A recent study done in 2019 showed that the visual acuity of presbyopes improved while wearing a novel accommodation-correction device 11 . The participants in that study also preferred wearing the accommodation-correction device over their regular prescription eyeglasses.…”
Section: Introductionmentioning
confidence: 99%